Perception of the Bible in the Symbolism of the Ukrainian Poetic Baroque (Linguostylistic Studies, 2020)
For the poets of the Baroque period, the Bible became a means of artistic expression of their feelings, their vision of the earthly, the real, and the divine, their understanding of the place of God in human life and the place of a human in the universe. Old Ukrainian literature actively used quotations from the Bible, its images, plots, and symbols. The symbols of Baroque poetry were ambiguous, arbitrary, and contradictory, like the epoch in which this poetry was created. The objectives of the article are: to determine semantic content of biblical symbols in the Ukrainian Baroque poetry, to offer reinterpretation to their meanings in the Ukrainian poetic discourse of the Baroque period, to clarify the stylistic functions of symbols. The symbolic images of the Ukrainian poetic Baroque have deep philosophical and biblical roots. Several semantic groups can be singled out here: 1) names of objects (bowl, cross, door, mirror, candle); 2) names of creatures (bird, wings, wolf, lamb, hen, shepherd); 3) names of plants (garden, vine, rose, lily, grass, flower); 4) astral names (sun). However, symbols appear on a certain national and historical basis and presuppose the common experience of the writer and the reader. A vivid example of this, in our opinion, is the symbol of a garden (in Ukrainian “sad”, rhyming with two other commonly used words, “vynohrad” and “vertohrad”). The symbolic perception of a garden is recorded in the Bible in the Song of Songs, in the Book of the Prophet Isaiah, and in the Gospel of St. John. In Baroque literature, the symbol of a garden has acquired an extraordinary semantic development. The garden was also called “vertohrad” – a word well known to the readers of the time. Therefore, poets calling their works “vertohrad” / “vynohrad” or using this image turned to the ideas that readers had already formed: Ñìеðòü, ÿê óæ, â òîì ñÿ ìëàäîì êðûåò âеðòîãðàäh - æ³é îïàñíî, ñе òè ãðîá â ñеì ïðеäëеæèò ñàäh (Українська (Крекотень) 37). Undoubtedly, for the contemporaries of the Baroque poets who knew the Bible and its image system well, biblical and artistic symbols meant more than for us, the people of the beginning of the XXI century, and therefore their artistic and aesthetic value was more significant. However, they are valuable components of the Ukrainian language worldview not only in the XVI–XVII centuries, but also in our historical path in literature and language. In this aspect, it will be promising to trace the durability of use of the analyzed symbols with established meanings in later poetic texts, and to follow the reinterpretation and the emergence of new meanings of symbols.
Keywords: linguistic stylistics; Baroque; Ukrainian poetry; symbol; Bible.